Increasing the Talent of High School Students through Islamic Counseling Guidance - Syarifuddin, Ummah karimah; Pawitri, Mutia (Journal of Islamic Communication and Counseling, 2022)
Students, especially high school students, will always be faced with several choices, both related to personal, social, study, career, and talent lives. They often have difficulty making decisions in determining which options to choose. One of them is the difficulty in understanding oneself related to his talent and the talent plans that will be selected for his future. Difficulties in making decisions when choosing talents can be avoided if students have a sufficient amount of information about matters relating to the world of their talents. Therefore they need to get development in their talent. This research uses the literature study method. The results of this study indicate that full Islamic guidance and counseling is needed as an effort to obtain an adequate understanding of various conditions and characteristics of himself, as a 'servant of Allah' who chooses nature (potential) both about talents, interests, ideas, various strengths and weaknesses. that is in him so as not to be wrong in developing his talents in accordance with Islamic guidance (Al-Qur'an and Hadith).